Ultraviolet B Radiation Triggers DNA Methylation Change and Affects Foraging Behavior of the Clonal Plant Glechoma longituba - Quan, Jiaxin; Latzel, Vít; Tie, Dan; Zhang, Yuhan; Münzbergová, Zuzana; Chai, Yongfu; Liu, Xiao; Yue, Ming (Frontiers in Plant Science, 2021)
Clonal plants in heterogeneous environments can benefit from their habitat selection behavior, which enables them to utilize patchily-distributed resources efficiently. It has been shown that such behavior can be strongly influenced by their memories on past environmental interactions. Epigenetic variation such as DNA methylation was proposed to be one of the mechanisms involved in the memory. Here, we explored whether the experience with Ultraviolet B (UV-B) radiation triggers epigenetic memory and affects clonal plants’ foraging behavior in UV-B heterogeneous environment. Parental ramets of Glechoma longituba were exposed to UV-B radiation for 15 days or not (controls), and their offspring ramets were allowed to choose light environment enriched with UV-B or not (the species is monopodial and can only chose one environment). Sizes and epigenetic profiles (based on methylation sensitive amplification polymorphism analysis) of parental and offspring plants from different environments were also analyzed. Parental ramets that have been exposed to UV-B radiation were smaller than ramets from control environment and produced less and smaller offspring ramets. Offspring ramets were placed more often into control light environment (88.46% ramets) than to UV-B light environment (11.54% ramets) when parental ramets were exposed to UV-B radiation, which is manifestation of “escape strategy”. Offspring of control parental ramets show similar preference to the two light environments. Parental ramets exposed to UV-B had lower levels of overall DNA methylation and had different epigenetic profiles than control parental ramets. The methylation of UV-B-stressed parental ramets was maintained among their offspring ramets, although the epigenetic differentiation was reduced after several asexual generations. The parental experience with the UV-B radiation strongly influenced foraging behavior. The memory on the previous environmental interaction enables clonal plants to better interact with heterogeneous environment and the memory is at least partly based on heritable epigenetic variation.